The power of community in the business professional to academic transition. Issue 5 (October 2020) - Bauer, Steven
Recent trends have made the transition from business professional to academic increasingly popular as a move to a second career. This article offers a personal perspective on a critical component of a successful transition—the fruitful leveraging of different university communities. The recommendations are in line with studies showing the importance of relationship variables to nontenure track faculty. The article also supports researchers who strive to create a stronger relationship between business and higher education institutions. The roles of departmental faculty mentors, faculty and administration in the larger university community, the student body community, and nonprofit organizations are discussed.